PENDEKATAN HOLISTIK VALUE PROPOSITION PENGGALIAN KEBUTUHAN SISTEM INFORMASI LEMBAGA KEMITRAAN DAN KAJIAN STRATEGIS PDM KOTA BATU - Wahyu Andhyka Kusuma; Agus Eko Minarno; Yufis Azhar; Denar Regata Akbi; Yuda Munarko; Ali Sofyan Kholimi; Zamah Sari; Syaifuddin Syaifuddin; Luqman Hakim (LPPM Universitas Nusa Mandiri, 2026)
The holistic value proposition approach to identifying the information system needs of the Lembaga Kemitraan dan Kajian Strategis (LKKS) of PDM Kota Batu is an initiative aimed at improving the efficiency and effectiveness of the institution's operations by developing an information system that has not yet been available within the organization. Information systems play an important role in supporting the institution's strategic activities and partnership programs. The community service method involved a series of in-depth interviews, focus group discussions, and surveys to identify users' primary needs and expectations regarding the information system. Pain and Gain analysis was employed to identify the strengths, weaknesses, opportunities, and threats associated with implementing the new information system. The results showed that the holistic value proposition approach successfully identified specific needs that were not only functionally relevant but also provided added value for all stakeholders. The implementation of the recommendations from the needs assessment is expected to improve institutional performance and collaboration. The holistic value proposition approach proved effective in identifying comprehensive information system needs and provides a strong foundation for developing a more responsive and value-added information system for LKKS PDM Kota Batu.